Damage modeling and critical damage evaluation of AA2014 cast alloy embedded with fly ash composite under upsetting. (August 2019) - HariKrishna, Ch; Davidson, MJ
Abstract: Upsetting is one of the primary metal forming techniques and needs to be applied to reduce the cross section of the billets for further processing. Ductile fracture in metal upsetting process is an issue and depends on the material used and processing conditions. The current work focus is on the critical damage evaluation of AA2014 cast alloy embedded with fly ash composite. AA2014 alloy was heated to a pouring temperature of 750 ℃ and fly ash of 3% and 6% were added separately with AA2014 matrix material to prepare three sets of cast alloys namely pure AA2014, AA2014 + 3% fly ash, and AA2014 + 6% fly ash. After manufacturing three sets of rods from stir casting process, three sets of billets were machined to a height and diameter of 24 mm. Three sets of billets were compressed between rigid dies to different levels of strain until the initiation of fracture. Ductile fracture criterions were modeled to evaluate the critical damage value and fracture loci were constructed for different compositions.